Sistem Informasi E-Office Berbasis Website Menggunakan Framework Codeigniter 3 Pada Universitas Pembangunan Jaya - Ahmad Al Khaidar; Rinna Rachmatika (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Pembangunan Jaya University (UPJ) is a private tertiary institution in the Bintaro area which was established in 2011 and is supported by the Jaya Development business group. At Pembangunan Jaya University there is an Administrative Governance process based on Excellent Service Standards. In this administrative governance there is still an administrative service process that has not been computerized, namely room borrowing services, tool lending and letter requests. Therefore, stakeholders must go to the place where the person in charge is to request paper from the service and ask for a signature of approval. So that it takes time for stakeholders to get information regarding which items are still available at a certain time, which tools can be borrowed and which stock is still available, and the process of submitting a letter of request. To improve quality and realize excellent service in the service governance process, an information system is needed which can help and facilitate stakeholders in going through the process. The system development method uses the Prototype method with system analysis and design using the Elicitation and UML approaches. The results of a web-based implementation were built using the PHP Programming Language with the use of CodeIgniter 3 Framework and MySQL database.